Investigating the heterodimerization process among receptors by Monte Carlo cellular automaton simulation - A. Wisitsorasak (2018)
It has become well known that simulation can be used to investigate complex biomedical systems in situations where traditional methodologies are difficult or too costly to be used. In this paper, Monte Carlo cellular automaton simulation is employed to study heterodimerization of receptor proteins. A computer program, based on a simple random walk of receptor molecules over a fixed lattice, has been written to simulate the diffusion and association of receptors over a two-dimensional membrane. The interaction and dynamics of these particles is in the form of the lattice Hamiltonian. The formation of two-dimensional clusters of receptors in a defined area of surface membrane is investigated. In particular, we measure the number of dimers throughout the dynamics and try to define the power law that governs the process.